2020
DOI: 10.3390/jcm9020381
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Transjugular Intrahepatic Portosystemic Shunt in Cirrhotic Patients 70 Years and Older

Abstract: Transjugular intrahepatic portosystemic shunt (TIPS) is effective at treating ascites and variceal bleeding but may be associated with increased morbidity and mortality in older patients. Our aim was to report outcomes in patients 70 years and older who underwent TIPS because data are limited in this population. We performed a retrospective review of patients who underwent TIPS at our institution over 10 years. We matched those 70 years and older to those 50–59 years old by year of TIPS and the Model for End-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Six studies with a total of 1,591 patients met our inclusion criteria and were included in the final meta-analysis [28][29][30][31][32][33]. Three studies divided patients by age < 65 vs. > 65 years, with a total of 816 patients who were 54% male.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies with a total of 1,591 patients met our inclusion criteria and were included in the final meta-analysis [28][29][30][31][32][33]. Three studies divided patients by age < 65 vs. > 65 years, with a total of 816 patients who were 54% male.…”
Section: Resultsmentioning
confidence: 99%
“…1) elaborates our systematic literature search process. Baseline characteristics, including patient demographics and indications for TIPS, are reported in Tables 2 and 3 [28][29][30][31][32][33]. Publication bias was not assessed due to the low number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another retrospective study in which the subjects were well matched for MELD score, indication for TIPS, and comorbidities showed that age is strongly and independently associated with 90-day post-TIPS mortality risk, particularly in those > 70 years[ 169 ]. Adlakha et al[ 170 ], in a retrospective study of 100 patients, similarly showed that re-admission rates and incidence of severe HE requiring hospital admission were higher in elderly patients, even after accounting for MELD score. They also found that TIPS for secondary prophylaxis of variceal bleeding, RA, and HH had acceptable morbidity and mortality.…”
Section: Considerations During Selection Of Patients For Tipsmentioning
confidence: 99%